2020
DOI: 10.31234/osf.io/epfbt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What processes are disrupted during the attentional blink? An integrative review of event-related potential research

Abstract: Reporting the second of two targets is impaired when these appear in close succession, a phenomenon known as the attentional blink (AB). Despite decades of research, what mechanisms are affected by the AB remains unclear. Specifically, two central issues remain open: Does the AB disrupt attentional processes or reflect a structural limitation in working memory encoding? Does it disrupt perceptual processing or only post-perceptual processes? We address these questions by reviewing event-related potentials (ERP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 85 publications
(198 reference statements)
2
5
1
Order By: Relevance
“…Thus, differences in visibility ratings cannot be attributed to differences in low-level visual processing of T2 stimuli. This result is consistent with overall evidence indicating that activity during the P1 time range is not modulated by the attentional blink (see Zivony & Lamy, 2020). In the consciousness literature as a whole, there also exists comparatively little evidence for differences in the P1 time range, and by now, there seems to be a growing consensus that the P1 is not a marker of conscious awareness (Förster et al, 2020;Koivisto & Revonsuo, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Thus, differences in visibility ratings cannot be attributed to differences in low-level visual processing of T2 stimuli. This result is consistent with overall evidence indicating that activity during the P1 time range is not modulated by the attentional blink (see Zivony & Lamy, 2020). In the consciousness literature as a whole, there also exists comparatively little evidence for differences in the P1 time range, and by now, there seems to be a growing consensus that the P1 is not a marker of conscious awareness (Förster et al, 2020;Koivisto & Revonsuo, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Already in the N1/N170 component, significant gradations of activity depending on the reported visibility were found. This effect stands in contrast to the attentional blink literature in general (when comparing "seen" and "unseen" trials) which overall indicates no differences during this time range (see Zivony & Lamy, 2020). In Sergent et al (2005), also no differences were observed in the N1 component.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations